Long-Term Sinonasal Function Following Transnasal Pituitary Surgery: A Comparison of Surgical Approach. Issue 3 (May 2020) - Cho, Jemma; Grayson, Jessica W.; Christensen, Jenna; Winder, Mark J.; Sheehy, John; Steel, Tim; Bentivoglio, Peter; Barham, Henry P.; McCormack, Ann; Harvey, Richard J.
Background: Surgical approaches to the pituitary have undergone significant changes from transcranial, sublabial, direct transnasal microscopic, and now endoscopic. This study compares sinonasal outcomes from patients from these techniques. Methods: A cross-sectional study of patients who underwent pituitary surgery in a tertiary setting was conducted. Patients were recruited via phone, mail, e-mail, and in person. Surveys with questions on nasal function, subsequent nasal treatment, the Nasal Symptom Score (NSS), Sinonasal Outcome Test-22 (SNOT-22), Chronic Sinusitis Survey (CSS), and Short Form 36 version 2 (SF-36v2) were obtained. Results: A total of 252 surveys were sent, of which 165 were returned (65.48% response rate) and 16 were excluded (3 records destroyed, 13 transcranial approach). A total of 149 patients (age 60.10 ± 13.99 years, 47.83% female) were assessed with the following breakdown: sublabial (n = 69), transnasal microscopic (n = 28), and endoscopic (n = 52) approaches. Sublabial and transnasal microscopic, compared to endoscopic, had more sinus treatment (30.43%, 39.29%, and 15.38%; P = .05), medication use (28.99%, 32.14%, and 11.54%; P = .04), and new allergy symptoms (21.74%, 7.14%, and 1.92%; P < .01). Compared to sublabial and transnasal microscopic, endoscopic patients had superior NSSs (0.40 [1.00], 0.60 [1.75], and 0.20 [0.60]; P = .05), SNOT-22 total scores (1.02 ± 0.58, 1.40 ± 0.78, and 1.00 ± 0.59; P < .01), and CSS medication subscores (100.00 [8.33], 100.00 [8.33], and 100.00 [0.00]; P = .03). Endoscopic patients also reported superior SF-36v2 physical subscores (44.02 ± 11.14, 41.13 ± 9.86, and 47.60 ± 10.12; P = .03). Conclusion: Nasal function was superior, and further sinus therapy and medication use was lower in patients with endoscopic approaches. Disease-specific quality of life was superior and the endoscopic approach resulted in reduced long-term sinonasal morbidity.